Design of low-voltage switched-capacitor filters - Loh, Nyean Wei. (2009)
This project aims to design a low voltage, fully differential switched capacitor (SC) filter with the use of standard 0.18!m CMOS technology. The approach of this project is to design a low voltage filter with 0.7V supply voltage using SC technology with Class C inverter amplifier for daily applications. The issues and challenges faced during designing a low power circuit will be discussed in the trend toward smaller and portable devices. Different topologies of amplifiers are being designed and investigated. The amplifiers include differential operational amplifier, fully differential operational amplifier and pseudo differential SC amplifier. The designed amplifiers with a supply voltage of 1.8V achieved an open loop of > 80 dB and with phase margin of > 60° while consuming a power of a milli-watt. The advantages, power consumption and drawbacks of the amplifiers are also observed in this report. The SC amplifier which consumed the lowest power, a few micro-watts (!W) will be use to implement the SC biquad filter. All the building blocks of the SC filter are also designed. The building blocks are clock generator, clock booster, transmission gates, SC amplifier, SC integrator and SC lossy integrator. Their purposes and advantages will be discussed. Three different topologies of SC biquad (second order) filter are designed. They are the conventional SC, the pseudo differential SC and the fully differential SC biquad filter. The proposed fully differential SC biquad filter can operate at 0.7V supply voltage with sampling frequency of 2.5MHz. The SC biquad filters consumed a power of about a few micro-watts. All the designed circuits’ schematic will be presented in this report.